Climate-growth relationships for Aspidosperma tomentosum Mart. in South American tropical dry forests - Lopez Callejas, Lidio (2020)
The precise demarcation and cross-dating of tree rings inAspidosperma tomentosumMart., a valuable timber species in the tropical dry forests of South America, were used to develop the first well-replicated chronology covering the period 1843?2015.A. tomentosumMart. tree growth is strongly regulated by soil water availability prior to and during the current growing season. In the context of increased drought severity due to climate change, determining of climate influences onA. tomentosumMart. radial growth is necessary to establish appropriate guidelines for the management, conservation and restoration of this species, currently affected by extreme weather events, extensive fires and deforestation in the Chiquitanía forests, Bolivia. Context: Tropical forest ecosystems play a critical role in the functioning of the Earth; thus, a better understanding of the influences of climate on tree growth is needed to estimate changes in forest productivity and consequently in carbon sink variations at regional and global scales. Aims: In the context of global environmental changes, our study aimed at using the growth rings of A. tomentosum Mart. to establish the relationships between radial growth and climatic variations. Methods: The anatomical characterization of the wood elements facilitated the precise annual band delimitation and the rejection of samples with false rings and growth anomalies. A tree-ring chronology was developed using traditional dendrochronological methods and the relationships with climate determined using correlation functions. Results: The chronology is based on 20 individuals and covers the period 1843?2015. Tree-ring statistics indicate an important common signal in growth variations between trees (R-bar = 0.31, EPS = 0.90). Interannual variations in A. tomentosum Mart. are directly related to total annual precipitation (r = 0.76) and inversely to mean annual temperature (r = − 0.44). These relationships are similar to those documented for other commercial species (Centrolobium microchaete, Schinopsis brasiliensis) from tropical dry forests in South America, suggesting a consistent climatic influence on tree growth at a regional scale. Conclusion: The strong dependence of tree growth on climate variability is a major concern, as climate change scenarios for tropical dry forests in South America predict an increase in the frequency and intensity of droughts, which in turn would reduce the A. tomentosum Mart. growth during the twenty-first century.